Can Artificial Intelligence Truly Assist in Surgery? A Deep Dive into the Operating Room of the Future - Rasit, Dinc (Rasit Dinc Digital Health & AI Research, 2024)
The integration of Artificial Intelligence AI into healthcare is rapidly transforming every facet of medicine, and the operating room is no exception. Once t...
Keywords: Diagnostics; Artificial Intelligence; Healthcare Innovation; Patient Care; Machine Learning